Upaya Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Biologi dengan Penerapan Model Pembelajaran Kooperatif Tipe STAD di kelas XII IPA MA Haasanah Pekanbaru TP 2021-2022 (Lembaga Anotero Scientific, 2022)
This action research is motivated by problems that arise in learning Biology in Class XII IPA students in the first semester of MA Hasanah Pekanbaru in the 2021/2022 academic year. These problems are low student motivation and interest in learning, low student learning outcomes. Some of the factors that cause these problems are: the delivery of material from the teacher is less varied, the teacher is not able to manage the class, the teacher is not guiding students in doing the exercises, the methods used by the teacher have not been able to increase student motivation and learning outcomes. Class action research with the application of the STAD type cooperative learning model aims to improve learning outcomes in biology subjects by applying the STAD type cooperative learning model to students of Class XII IPA semester I MA Hasanah Pekanbaru in the 2021/2022 academic year. Accordingly, the procedure for carrying out this research is manifested in the form of continuous and continuous cycle stages, where each cycle consists of 4 (four) stages which in outline are: 1) planning corrective actions, 2) implementing or implementing planned actions, 3) observing or observing corrective actions taken, and 4) reflecting, including analysis, interpretation and evaluation of actions taken. The main conclusions generated in this classroom action research are answers to the research problems that have been formulated, as follows: The application of the STAD type cooperative learning model can improve learning outcomes in Biology subjects in Class XII IPA IPA MA Hasanah Pekanbaru in the 2021/2022 academic year. This formulation is acceptable, because learning outcomes increase. Student completeness prior to improvement was only 8 (47%). In cycle I, 12 students (71%) complete learning. Improvements in cycle II, student learning completeness by 17 (100%). Likewise with the absorption of students, before the improvement of students' absorption was only (75%). Improvements in the first cycle of student absorption (79%). Improvements in cycle II, student absorption (86%).